Industry Specificity As A Factor Differentiating Employment Effects In Special Economic Zones (Sezs) Firms - Marlena Cicha-Nazarczuk (Communications of International Proceedings, 2025)
The aim of this study was to determine whether and to what extent the industry can influence the employment effects of firms benefiting from support within special economic zones (SEZs) in Poland. In-depth analyses considering the impact of industry on the effectiveness of support programmes at the microeconomic level are lacking in the literature to date. The analysis uses a counterfactual approach based on propensity score matching (PSM) with a kernel estimator and the difference-in-difference (DiD) method to estimate the net effects of SEZs at the firm level. The empirical results show that industry significantly differentiates the effect of SEZs on employment - in some industries the effect is positive and statistically significant, in others it is neutral or insignificant. This means that the effectiveness of public support depends on the specifics of the industry, and standardised support instruments are not equally effective for all actors. The conclusions of the study point to the need to tailor SEZ policies to sectoral characteristics, which may increase their impact on job creation, innovation and productivity.
Keywords: special economic zones; regional policy; labour market; employment; industry; evaluation.